Combination of oral zinc gluconate and topical triclosan: An anti-inflammatory treatment modality for initial hidradenitis suppurativa. Issue 2 (November 2016) - Hessam, Schapoor; Sand, Michael; Meier, Nina Mareike; Gambichler, Thilo; Scholl, Lisa; Bechara, Falk G.
Highlights: Hidradenitis suppurativa (HS) is often a therapeutic challenge. An effective anti-inflammatory treatment in initial cases is needed. Zinc gluconate and topical triclosan significantly decreased disease severity score (mHSS). In addition, quality of life (DLQI) was significantly improved. Combination therapy expands treatment in Hurley stage I and initial stage II. Abstract: Background: Hidradenitis suppurativa (HS) is often a therapeutic challenge with relapses and chronicity which can severely impact patients' quality of life. Objective: To evaluate the efficacy of anti-inflammatory oral zinc gluconate, 90 mg/day, combined with topical triclosan, 2% twice daily. Methods: We retrospectively evaluated the medical records of HS patients in our HS Center of the Department of Dermatology, Venereology, and Allergology, Ruhr-University Bochum, regarding change of disease severity and quality of life. Secondary outcome measures were the number of nodules and fistulas, the number of boils or flair-ups, and the intensity of pain. Results: Sixty-six patients in Hurley stage I and II were included. After 3 months of combination therapy, the modified HS Score and the Dermatology Life Quality Index improved significantly (p < 0.0001 and p = 0.0386, respectively). The number of inflammatory nodules, new boils or flare-ups, and erythema scores decreased significantly. Fistula count and the visual analogue scale score showed no significant difference. Side-effects (mostly abdominal pain and nausea) were reported by 12 (22.2%) patients. Conclusion: The combination therapy of zinc gluconate and topical triclosan can be considered as an anti-inflammatory treatment for HS patients in Hurley stage I and initial Hurley stage II.